Model For Identification Of Management Degree In Brazilian Coffee Production - Antonio Bliska; Antonio Ferraz; Paulo Leal; Flavia Bliska (European Regional Science Association (ERSA), 2012)
In Brazil, coffee is one of the most important crops, particularly regarding job creation and foreign exchange. Since its introduction in the country in 1727, in the North region, the coffee cultivation is spread over much of the Brazilian territory. Over nearly 300 years, coffee production has developed with different costs and competitiveness, resulting mainly from soil and climatic conditions and different levels of technology, international competition and pricing, government incentives, investments in scientific and technological development, as well as different levels of entrepreneurship, which are reflected in the degree of agribusiness management and are extremely important to increase their competitiveness and survival. Cooperatives and the coffee industry consultants have developed systems to assist the farmer in company management, particularly with respect to the systematization of production costs and planning activities for the agricultural year. But the methods developed do not provide information about the level of company management, particularly regarding quality. To overcome this deficiency, this study aims to develop a simple, easy to use and inexpensive method to analyze the points to be improved regarding the management of the property, even if it is not exhaustive. Thus, farmers may adopt foundations, criteria and quality management practices that result in the organization of their companies and contribute to local and regional rural development. This study is centred on rural production, for reflections of the implementation of concepts and practices of agribusiness management, aiming at the obtaining of high quality products, permeate the sector as a whole. This method, named Method of Identification of Management Degree (MIMG), consists of a questionnaire, originally developed for application in cut flowers sector. Later it was used in the production of flowers in pots and hydroponics and after that, adapted to coffee production. A questionnaire was compiled using specific methodologies to collect primary and secondary data, plus the Delphi technique, which was employed to establish priorities and hierarchy of parameters of the management of an agricultural enterprise. This questionnaire was distributed to experts of the coffee sector to rank the parameters, which were transformed into objective questions used to construct a second questionnaire to be filled in by the organizations directly involved in the activity. This questionnaire, associated to a score table, indicates the managerial maturity degree of the organizations and points out the opportunities for process improvements.
Keywords: 330